Scalpel, please: How do surgeons communicate and interact with robotic scrub nurses during instrument handoffs in intraoperative care - Riener, Kurtis W.; Hjalmarson, Dori; Luo, Yue (Proceedings of the International Symposium of Human Factors and Ergonomics in Healthcare, 2025)
Robotic scrub nurse systems are an emerging technology that mark an opportunity to ease the staffing burdens hospitals are facing across the globe while upholding quality of care and protecting patient safety. Our aim is (1) to develop a consolidated source of information on how these systems communicate and interact with surgeons during instrument handoffs and (2) provide design considerations to benefit future designers of these systems. In pursuit of these aims, we’ve produced a scoping review exploring the topic. We found that surgeons communicate with robotic scrub nurses through three main modalities (e.g., gesture, voice, gaze) and that communication flowing from robotic scrub nurse to surgeon is limited. Furthermore, while the actual process of handoffs seems sound, current systems cannot handle a sufficient amount of instruments or handle the return of instruments. We conclude our work by leveraging our findings to provide pertinent design considerations relating to communication between surgeon and robot and the properties of the robots themselves in order to improve the fidelity of future systems.